2020
DOI: 10.3390/w12092488
|View full text |Cite
|
Sign up to set email alerts
|

Water of Increased Content of Molecular Oxygen

Abstract: Deionized and tap water were saturated with molecular oxygen either prior to (WST), or after (WTS), treatment with low-temperature, low-pressure glow plasma of low frequency (LPGP) for 0, 5, 15, 30, 60, 90, and 120 min. Physical and physicochemical properties of the resulting liquids were characterized, involving pH, conductivity, density, dissolved molecular oxygen, active oxygen content, differential scanning calorimetry (DSC), ultraviolet-visible (UV-VIS), Fourier transformation infrared-attenuated total re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A large amount of evidence has been collected, suggesting that mechanical stress can affect the properties of biomolecules and cells (Dotsenko & Mischenko, 2011;Dotsenko et al, 2014;Bunkin et al, 2020). Erythrocytes exposed to vibration were kept in buffer solution saturated with O 2 (Chwastowski et al, 2020). O 2 itself, along with other gases, is found in bubbles with the diameter of less than a micron -nanobubbles (Bunkin et al, 2011;Shatalov et al, 2012;Li & Bunkin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of evidence has been collected, suggesting that mechanical stress can affect the properties of biomolecules and cells (Dotsenko & Mischenko, 2011;Dotsenko et al, 2014;Bunkin et al, 2020). Erythrocytes exposed to vibration were kept in buffer solution saturated with O 2 (Chwastowski et al, 2020). O 2 itself, along with other gases, is found in bubbles with the diameter of less than a micron -nanobubbles (Bunkin et al, 2011;Shatalov et al, 2012;Li & Bunkin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Water treated for the same time with LGPG under nitrogen as described by Chwastowski et al, [7] produced LPGPN. LPGPC [13], LPGPO [9] and LPGPM [12] were prepared following the procedures described in the indicated references. LPGP of 38 • C was generated at 5 × 10 −3 mbar, 800 V, 50 mA and 10 KHz frequency in a plasmothrone patented by Oszczęda et al [1,10].…”
Section: Watermentioning
confidence: 99%
“…LPGP was found to be different to other reported kinds of plasma [2][3][4][5][6] (see also the relevant literature survey in our recent paper [7]) because it does not break valence bonds; therefore, treatment with LPGP does not evoke any chemical reaction. Thus, single oxygen atoms, hydrogen peroxide and ozone cannot be formed when water is treated with LPGP in the air [8], as well as under molecular oxygen [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the invention of low-temperature, low-pressure glow plasma of low frequency (LPGP) and the constructing of generators for such plasma [1,2], a series of papers was published describing the macrostructure and the resulting physical, physicochemical and chemical properties of water treated with LPGP. It appeared that these properties depended, among other things, on whether that treatment was performed in the air, under nitrogen, ammonia, carbon dioxide, methane or molecular oxygen [3][4][5][6][7][8]. Subsequent papers demonstrated that these diverse properties resulted in specific functional properties for different kinds of water.…”
Section: Introductionmentioning
confidence: 99%